[2.2]Paracyclophane‐Based TCN‐201 Analogs as GluN2A‐Selective NMDA Receptor Antagonists. (3rd August 2021) - Rajan, Remya; Schepmann, Dirk; Steigerwald, Ruben; Schreiber, Julian A.; El‐Awaad, Ehab; Jose, Joachim; Seebohm, Guiscard; Wünsch, Bernhard
Abstract: Recent studies have shown the involvement of GluN2A subunit‐containing NMDA receptors in various neurological and pathological disorders. In the X‐ray crystal structure, TCN‐201 (1 ) and analogous pyrazine derivatives 2 and 3 adopt a U‐shape (hairpin) conformation within the binding site formed by the ligand binding domains of the GluN1 and GluN2A subunits. In order to mimic the resulting π/π‐interactions of two aromatic rings in the binding site, a [2.2]paracyclophane system was designed to lock these aromatic rings in a parallel orientation. Acylation of [2.2]paracyclophane (5 ) with oxalyl chloride and chloroacetyl chloride and subsequent transformations led to the oxalamide 7, triazole 10 and benzamides 12 . The GluN2A inhibitory activities of the paracyclophane derivatives were tested with two‐electrode voltage clamp electrophysiology using Xenopus laevis oocytes expressing selectively functional NMDA receptors with GluN2A subunit. The o ‐iodobenzamide 12 b with the highest similarity to TCN‐201 showed the highest GuN2A inhibitory activity of this series of compounds. At a concentration of 10 μM, 12 b reached 36 % of the inhibitory activity of TCN‐201 (1 ). This result indicates that the [2.2]paracyclophane system is well accepted by the TCN‐201 binding site. Abstract : In the binding pocket of crystallized GluN1/GluN2A ligand binding domain, the prototypical antagonist TCN‐201 and analogs adopt a U‐shaped conformation. [2.2]Paracyclophane‐based GluN2A antagonists were designed to mimic the U‐shaped conformation of TCN‐201 in the binding pocket. The synthesized benzamide shown here possesses 36 % of the GluN2A inhibitory activity of TCN‐201, confirming that compounds with the [2.2]paracyclophane system are well accepted by GluN2A‐NMDA receptors.